2010
DOI: 10.1073/pnas.0911109107
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of alcohol dependence

Abstract: Excessive alcohol consumption is one of the leading causes of preventable death in the United States. Approximately 14% of those who use alcohol meet criteria during their lifetime for alcohol dependence, which is characterized by tolerance, withdrawal, inability to stop drinking, and continued drinking despite serious psychological or physiological problems. We explored genetic influences on alcohol dependence among 1,897 European-American and African-American subjects with alcohol dependence compared with 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
466
4
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 414 publications
(492 citation statements)
references
References 45 publications
19
466
4
3
Order By: Relevance
“…Accordingly, any single gene contributes only to a limited extent to the phenotypes observed in alcohol consumption (6). In contrast to alcohol addiction, which has been investigated in numerous genetic studies (5), including recent genome-wide association studies (GWAS) analyses (7)(8)(9), few genes regulating alcohol consumption in humans have been described-with the notable exception of alcohol dehydrogenase (3,5,10). This may, to some extent, reflect the complexity of the phenotype, because the genetic and environmental determinants of alcohol drinking behavior may vary over the lifespan, and there may be substantial heterogeneity of intake and measurement across different populations and studies.…”
mentioning
confidence: 99%
“…Accordingly, any single gene contributes only to a limited extent to the phenotypes observed in alcohol consumption (6). In contrast to alcohol addiction, which has been investigated in numerous genetic studies (5), including recent genome-wide association studies (GWAS) analyses (7)(8)(9), few genes regulating alcohol consumption in humans have been described-with the notable exception of alcohol dehydrogenase (3,5,10). This may, to some extent, reflect the complexity of the phenotype, because the genetic and environmental determinants of alcohol drinking behavior may vary over the lifespan, and there may be substantial heterogeneity of intake and measurement across different populations and studies.…”
mentioning
confidence: 99%
“…19 The control data set included Affymetrix SNP 6.0 (Affymetrix, Santa Clara, CA, USA) data from 1123 controls recruited from northern Germany as a part of the PopGen project, 20 1234 healthy controls recruited from the province of Ontario (Canada) for a coronary artery disease study by the Ottawa Heart Institute (OHI), 21 and 4783 British controls from the Wellcome Trust Case Control Consortium (WTCCC), 16 and Illumina Infinium 1 M (Illumina Inc., San Diego, CA, USA) data from 1287 controls recruited by the Study of Addiction: Genetics and Environment (SAGE) consortium. 22 No CNVs were detected in these controls of comparable size and extent as the 2q23.1 duplications in these two patients. There were six small intragenic variants of sizes o100 kb, which did not overlap with any of the genes in the region.…”
Section: Control Populationsmentioning
confidence: 98%
“…7,10,11 The relevant role of genetic factors both on alcohol consumption and dependence has been clearly demonstrated by genome-wide association study (GWAS) studies. [12][13][14][15][16] Moreover, studies on the genetic variations in bitter taste receptors have also shown that variations in TAS2R16 and TAS2R38 genes can influence alcohol intake [17][18][19] but not dependence. 19 On the contrary, very little is known about the possible contribution of genetic factors to alcohol preferences in humans.…”
Section: Introductionmentioning
confidence: 99%